STUDI TENTANG ANALISIS KOMPETENSI PEDAGOGIK DAN KOMPETENSI PROFESIONAL GURU PENDIDIKAN AGAMA ISLAM SMP DI KOTA PALU - Hamzah Hamzah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2015)
To be able to build quality human resources, the role of education is a very important factor. The current education system in Indonesia is still facing a very complex challenges related to the low quality and relevance of education. However, with the implementation of the law of Teachers and Lecturers will allow teachers to have strong positions like other professions, so it is possible pedagogic competence and professional competence of teachers will increase along with a certification process that has been put in place.The problem in this research is how the level of mastery of pedagogical competence of teachers of Islamic education junior high school in the city of Palu, and how the level of mastery of professional competence of teachers of Islamic education in junior high school in Palu.The purpose of this study was to describe the level of mastery of pedagogical competence of teachers of Islamic education in junior high school in the city of Palu, and to describe the level of mastery of professional competence of teachers of Islamic education in junior high school in Palu.The method used is the qualitative approach, then to obtain data in accordance with problems, data collection techniques is done by observation, questionnaires, interviews, and documentation. Then proceed with the data analysis.Results and findings of the research show that teachers have pedagogical competence Islamic education in junior high school in Palu are generally classified as moderate and fairly nice, except the educational aspects of learning that there are some aspects that have not been too occupied. Furthermore, professional competence held by teachers of Islamic education in junior high school in Palu is generally considered high by some findings through questionnaires and interviews